Use of CRISPR-CAS9 system in groundnut (Arachis hypogaea) transformation targeting ahFAD2 gene: Use of CRISPR-CAS9 system in groundnut (Arachis hypogaea) transformation targeting ahFAD2 gene - RIDDHI H RAJYAGURU; RUKAM S TOMAR (Journal of Oilseeds Research, 2020)
Down regulation of ahFAD2 results in reduced conversion of oleic to linoleic acid thus enhancing O/L ratio in groundnut. Novel gene editing technique, CRISPR-CAS9 was used to edit ahFAD2 gene in groundnut to enhance O/L ratio. Guide RNA (gRNA) was identified and designed targeting 1200 bp within the 1710 bp long ahFAD2 gene. Later, gRNA was successfully cloned into p53 construct having, CAS9. Entire construct was transferred into Agrobacterium and validated using PCR primers. Explants co-cultured with Agrobacterium, produced multiple shoots. Transformed shoots were selected on hygromycin selective media.